Reduction of extinction and reinstatement of cocaine seeking by wheel running in female rats - Zlebnik, Natalie E. (2010)
RATIONALE AND OBJECTIVES: Previous work has shown that wheel running reduced the maintenance of cocaine self-administration in rats. In the present study, the effect of wheel running on extinction and reinstatement of cocaine seeking was examined. Female rats were trained to run in a wheel during 6-h sessions, and they were then catheterized and placed in an operant conditioning chamber where they did not have access to the wheel but were allowed to self-administer iv cocaine. Subsequently, rats were divided into four groups and were tested on the extinction and reinstatement of cocaine seeking while they had varying access to a wheel in an adjoining compartment. The four groups were assigned to the following wheel access conditions: (1) wheel running during extinction and reinstatement (WER), (2) wheel running during extinction and a locked wheel during reinstatement (WE), (3) locked wheel during extinction and wheel running during reinstatement (WR), and (4) locked wheel during extinction and reinstatement (WL). WE and WR were retested later to examine the effect of one session of wheel access on cocaine-primed reinstatement. RESULTS: There were no group differences in wheel revolutions, in rate of acquisition of cocaine self-administration, or in responding during maintenance when there was no wheel access. However, during extinction, WE and WER responded less than WR and WL. WR and WER had lower cocaine-primed reinstatement than WE and WL. One session of wheel exposure in WE also suppressed cocaine-primed reinstatement. CONCLUSIONS: Wheel running immediately and effectively reduced cocaine-seeking behavior, but concurrent access to running was necessary. Thus, exercise is a useful and self-sustaining intervention to reduce cocaine-seeking behavior.